Recalling the Definitions with a Mind Mapping and SelfLearning Technique: A Comparative Study in Undergraduate Students - Merlin Suji1 , Sharadha Ramesh2 , Seeta Devi3 , Diana Prasad1 , Leeja Rajan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Around 13.34% weightage is given to the definitions of university exams in nursing.1Nursing educatorsneed to help the students in memorizing terms, so that students can write the correct concept in the exameffectively.Aim: To assess the comparison of mind mapping and self-learning techniques in recalling thedefinition. Design : A comparative approach was used to understand the difference between the knowledgeof self-learning group and mind mapping group . Total 5 definitions were used from the nursing foundationtextbook .To obtain baseline data, subjects completed a short test and it is randomly allocated to two groups:‘self -learning’ and ‘mind map’. After a one hour of study period short test was taken. Recalling wasmeasured after a week later. Setting: Symbiosis College of Nursing, Symbiosis International University,India. Subjects : 48 First year Bachelor Nursing Students. Results: Mean score in Mind mapping groupwere 5.87 and 5 in session one and two . For self-learning group, the mean effect was 6.21and 4.67 in the firstand second sessions. Hence Mind mapping technique proven to be more effective than Self learning methodin recalling the definition. Two sample t-test for comparison of effect of Mind mapping vs self-learningmethod.t-values for this comparison were –0.76 and 0.62 . Corresponding p-values were 0.45 and 0.54 andthe p-value < 0.05 , so the null hypothesis is rejected. Conclusion: mind maps were proved affectivity as away of recalling the definitions in the second session. Students need to be encouraged to adopt this approachmore than the other conventional learning techniques.